Rota das edificações católicas em Silveira Martins/RS: caracterização do patrimônio e da paisagem cultural - Pissutti, Marcelo (2020)
The study aimed to feature the cultural heritage and scenery along the route of existing Catholic buildings in Silveira Martins - RS county, as a way of supporting sustainable preservation. Therefore, a qualitative methodological approach was used, whose research was operationalized through a case study. The sources consisted of bibliographic and documentary surveys, on-site observations, iconography (photographic, map and floor plan surveys), inventory sheets and local community interviews. A combination of multiple sources was critical to the success of the research. In this sense, regarding the results, it was possible to describe the municipality's context and identify sixteen Catholic buildings existing in its territory, in order to inventory the architectural heritage. Then, the buildings identified were characterized in terms of access, surroundings, history, architectural and photographic surveys, celebrations and religious activities. Finally, the cultural landscape of the route of Catholic buildings in the municipality was characterized, integrating the different natural, cultural and economic aspects that surround them, as a way of supporting sustainable preservation. In this way, it was possible to identify a complex web that integrates the buildings and their landscape, as well as draw it’s associated practices. It was identified that the context of the buildings permeates the history of Italian immigration to the extent that they materialize (and immaterialize) the faith that the first immigrants brought with them in the holds of ships. Faith, added to the perpetuity of the culture and identity of a people, were aspects that kept them in the territory of the Fourth Colony of Italian Immigration. The inventoried temples proved to be places to exercise the sacred, but also, in an overlapping way, to social and cultural functions. They are meeting places that integrate and maintain the habits and customs associated with the community in the region. In face of what was found, considering that the buildings and their social practices are woven into an attractive landscape, the approach of cultural routes or itineraries proved to be relevant. This perspective included an integrated analysis of heritage and cultural landscapes that can promote tourism and, mainly, the perpetuity of the context in which the buildings are inserted, supporting their sustainable preservation.